Credit for agricultural development - Khandker, Shahidur R. (International Food Policy Research Institute, 2021)
Access to financial services is critical for agricultural development. By “access to financial services” we mean access to credit, savings, payments, and insurance. Such a broad measure of access is called “financial inclusion” in the recent development literature. Financial inclusion is also defined as a measure of an individual’s and a business’s access to use of financial services to save, borrow, make payments, and buy insurance to mitigate risk in production and consumption (Demirguc-Kunt and Klapper 2012; Demirguc-Kunt et al. 2015).1 Access to financial services facilitates an individual’s and a business’s day-to-day transactions and helps them manage everything from investment plans to unexpected emergencies. “Financial access” means access to outlets where people save, borrow, pay bills, and buy insurance, in order to initiate and expand businesses, to invest in education or health, to manage risk, and to weather shocks. All these activities induced by financial inclusion lead to higher productivity, raising income, consumption, nutrition, and education, and thus achieving multiple Sustainable Development Goals (World Bank 2018).